Research Quality Assurance In Arabic World : Analgtical At Field Study - Mustafa Altabeb (University of Science and Technology, Yemen, 2013)
Abstract: The current study focused its attention on ensuring the quality of scientific research, as a basic rule in the progress of humanity and the researchers know the quality assurance: as The level at which you can has a set  of specifications from the completion of a pre-set targets, of  the general direction, and strategic goals, or set of goals of knowledge and skills to achieve desired, This study aims to recognize the reality of scientific research in the Arab world at the present time, analysis of the main problems encountered, It also aims to identify a mechanism to improve the quality of scientific research, through a poll of university staff members about three dimensions contribute effectively to the development of research in the Arab world, namely: (Respect to the educational aspect Scholar and Research Foundation, and expenditure on scientific research, and the political side), , And the researcher dealt with in the current study, two aspects: first respect to analysis of the current status of scientific research, and problems encountered, and the second is in the field study, which aimed to explore a sample of (120) professors at universities Libyan on how to develop scientific research, the study found the following results: 1. The study saw a sample focus on the Arab researcher and Research Foundation. 2. The study found that the focus on funding or expenditure is an important aspect to ensure the quality of scientific research in the Arab world. • 3.  Focus on the political stability of the Arab States. The study found a set of recommendations was in the situation of scientific research on the priority list of Arab countries, and interest in research Foundation, and the provision of periodicals and scientific journals.